2004
DOI: 10.1189/jlb.0204065
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 regulates expression of the CXC chemokine LIX/CXCL5 in osteoblasts: implications for inflammation and neutrophil recruitment

Abstract: Interleukin (IL)-17 is the founding member of an emerging family of inflammatory cytokines whose functions remain poorly defined. IL-17 has been linked to the pathogenesis of rheumatoid arthritis, and numerous studies implicate this cytokine in inflammation-induced bone loss. It is clear that a major function of IL-17 is to amplify the immune response by triggering production of chemokines, cytokines, and cell-surface markers, ultimately leading to neutrophil chemotaxis and inflammation. As an IL-17 signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
135
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(142 citation statements)
references
References 66 publications
5
135
0
2
Order By: Relevance
“…Recent studies demonstrated that IL-17 induces the release by joint structural and resident cells (e.g., chondrocytes, synovial fibroblasts, and macrophages) of several inflammatory mediators, including cytokines (e.g., TNF␣) and chemokines (e.g., CXCL1 and CXCL5), which may recruit neutrophils (42,43). Here we identify the mediators downstream of IL-17 participating in the neutrophil migration to the joint cavities in AIA.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies demonstrated that IL-17 induces the release by joint structural and resident cells (e.g., chondrocytes, synovial fibroblasts, and macrophages) of several inflammatory mediators, including cytokines (e.g., TNF␣) and chemokines (e.g., CXCL1 and CXCL5), which may recruit neutrophils (42,43). Here we identify the mediators downstream of IL-17 participating in the neutrophil migration to the joint cavities in AIA.…”
Section: Discussionmentioning
confidence: 95%
“…This may be particularly important in light of IL-17 and TNF␣ synergy. Nearly all IL-17-induced genes that we have examined exhibit additive or synergistic induction when combined with TNF␣ (6,19,53). Several mechanisms of cooperative activity have been proposed, such as cooperative enhancement of mRNA stability and/or activation of the p38 MAPK pathway (37, 38, 40, 54 -56).…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-17 together with TNFα stabilizes IL-6 mRNA [71,[76][77][78]. Similarly, IL-17 serves to enhance mRNA stability of transcripts encoding G-CSF [79], GM-CSF [80], CXCL1/KC/Groα [81], CXCL5/LIX [82,83], IL-8 [77], IκBζ [84] and COX-2 [85,86]. Considerable data implicate MAPK pathways in mRNA stabilization effects.…”
Section: Il-17 Regulates Inflammatory Genes Through Synergistic Signamentioning
confidence: 99%